2007
DOI: 10.1038/nature05886
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomally unstable mouse tumours have genomic alterations similar to diverse human cancers

Abstract: Highly rearranged and mutated cancer genomes present major challenges in the identification of pathogenetic events driving the neoplastic transformation process. Here we engineered lymphoma-prone mice with chromosomal instability to assess the usefulness of mouse models in cancer gene discovery and the extent of cross-species overlap in cancer-associated copy number aberrations. Along with targeted re-sequencing, our comparative oncogenomic studies identified FBXW7 and PTEN to be commonly deleted both in murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
336
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(358 citation statements)
references
References 48 publications
(71 reference statements)
18
336
4
Order By: Relevance
“…Second, there are intrinsic differences in the stability of human and mouse cancer genomes. 71 Human cancer genomes are typically structurally complex, with numerous regions of focal chromosomal gain and loss; however, only a small subset of these copy number changes affect driver genes ( Figure 2). In contrast, mouse cancer genomes tend to have whole chromosome gains or losses, with few focal copy number variations.…”
Section: Selecting An Animal Model That Maximizes the Advantages Of Cmentioning
confidence: 99%
“…Second, there are intrinsic differences in the stability of human and mouse cancer genomes. 71 Human cancer genomes are typically structurally complex, with numerous regions of focal chromosomal gain and loss; however, only a small subset of these copy number changes affect driver genes ( Figure 2). In contrast, mouse cancer genomes tend to have whole chromosome gains or losses, with few focal copy number variations.…”
Section: Selecting An Animal Model That Maximizes the Advantages Of Cmentioning
confidence: 99%
“…However, results from our lab show that non-deletional inactivation of PTEN is a major contributor to hyperactivation of PI3K/Akt in primary T-ALL samples (Silva A, Yunes JA, Cardoso BA, Martins LR, Jotta PY, Abecasis M, Nowill AE, Leslie NR, Cardoso AA, Barata JT, unpublished data). PTEN mutations resulting in protein truncation have been identified more frequently in T-ALL cell lines established from relapsed patients (30.4%) than in diagnostic clinical specimens (5.2%), which suggests that PTEN deletion is a late event in human T-ALL (25). In contrast, recent studies using mouse models have shown that PTEN deregulation is important at early stages of leukemogenesis.…”
Section: Pi3k/aktmentioning
confidence: 75%
“…Nevertheless, no activating mutations of PI3K and/or Akt have been described in T-ALL. It has been suggested that PI3K/Akt pathway over-activation results from PTEN protein downregulation and/or SHIP mutations (25,26). However, results from our lab show that non-deletional inactivation of PTEN is a major contributor to hyperactivation of PI3K/Akt in primary T-ALL samples (Silva A, Yunes JA, Cardoso BA, Martins LR, Jotta PY, Abecasis M, Nowill AE, Leslie NR, Cardoso AA, Barata JT, unpublished data).…”
Section: Pi3k/aktmentioning
confidence: 99%
“…Nedd9 encodes a signaling protein that enhances invasion and metastasis when overexpressed in melanocytes [26]. In the future, introduction of genomic instability into mouse models will enable increased utility of this crossspecies approach [27].…”
Section: Copy Number Alteration Profilingmentioning
confidence: 99%